Development of the Production of Curcumin Powder for Application in the Food Industry - Alwani Hamad; Afwa Hayuningtyas; Bekti Wulan Sari; Mubshair Naveed (Research in Chemical Engineering, 2023)
Curcumin has been identified as the most abundant bioactive constituent in turmeric (Curcuma longa) extract (2 - 8% w/w). Curcumin is used as a preservative, flavoring, and yellowish colorant agent in the food industry. Modern scientific studies have confirmed its anti-inflammatory, antioxidant, anti-carcinogenic, and antimicrobial properties. Curcumin is easily oxidized and light-damaged, and it is insoluble in water. This product's shelf life should be increased. Curcumin microencapsulation into powder solves these issues. This process has been used because of its low cost, equipment availability, continuous production, and ease of industry. Curcumin powder in food could be crude turmeric powder (0.58 - 3.14%w/w), curry powder (0.11 - 0.58%w/w), or spray dried turmeric oleoresin curcumin powder (40 - 50%w/w). Spray drying coats the curcumin core material into the matrix powder, improving stability. The wall material (gum arabic, maltodextrin, or chitosan) and emulsifying agent were dispersed in continuous phase with the curcumin core material to prepare the microencapsulated flowing powders. Several formulation modifications in spray drying methods, such as co-dried and binary blend materials, have been investigated to improve the stability of curcumin. Curcumin powder is becoming more popular as a treatment for a variety of ailments, as well as a compound that is generally regarded as safe. As a result, its application as a nutraceutical or functional food has the potential to be expanded further.